Use of the RCOG risk assessment model and biomarkers to evaluate the risk of postpartum venous thromboembolism - Hua Li; Sheng Wan; Jindan Pei; Lu Zhang; Jing Peng; Ronghua Che (Thrombosis Journal, 2023)
Abstract Background Venous thromboembolism (VTE) is a leading cause of morbidity and mortality during pregnancy and the puerperium. The vast majority of VTE occurs after childbirth. China has not yet established standard risk assessment model for postpartum venous thromboembolism (VTE), the Royal College of Obstetricians and Gynecologists (RCOG) risk assessment model (RAM) is commonly used in clinic at present. Herein, we aimed to evaluate the validity of the RCOG RAM in the Chinese population and try to formulate a local risk assessment model by combining with other biomarkers for VTE prophylaxis. Methods The retrospective study was conducted from January 2019 to December 2021at Shanghai First Maternity and Infant Hospital which has approximately 30,000 births annually, and the incidence of VTE, differences between RCOG-recommended risk factors, and other biological indicators from medical records were evaluated. Results The study included VTE (n = 146) and non-VTE(n = 413) women who examined by imaging for suspicion of postpartum VTE. There was no statistical difference in the incidence rate of postpartum VTE between the low-score group (23.8%) and the high-score group (28%) after stratification by RCOG RAM. However, we found that cesarean section (in the low-score group), white blood cell (WBC) ≥ 8.64*10^9/L (in the high-score group), low-density lipoprotein(LDL) ≥ 2.70 mmol/L, and D-dimer ≥ 3.04 mg/L (in both groups) were highly associated with postpartum VTE. Subsequently, the validity of the RCOG RAM combined with biomarkers as a model for the risk assessment of VTE was estimated and the results showed that this model has good accuracy, sensitivity, and specificity. Conclusions Our study indicated that the RCOG RAM was not the best strategy for predicting postpartum VTE. Combined with some biomarkers (including the value of LDL and D-Dimer, and WBC count), the RCOG RAM is more efficient when identifying high-risk groups of postpartum VTE in the Chinese population. Trial registration This purely observational study does not require registration based on ICMJE guidelines.